Permainan Stereotipe Gender: Studi Kasus Performativitas dalam Pertunjukan Wayang Kulit Ki Seno Nugroho - Indah Ayu Fitria; Timbul Haryono; Vissia Ita Yulianto (Institut Seni Indonesia Yogyakarta, 2021)
AbstractThis paper discusses sinden’s role and position in shadow puppet shows in the current era, with a case study of sinden on ki Seno Nugroho’s show. Butler’s gender performance theory is used to look at the performance power of sinden-sinden Ki Seno Nugroho (Apri-Mimin “the male sinden duo”and Elisha “sulawesi sinden”). Butler in theory stated that gender performanceivity was initiated to dismantle the problem of gender construction hierarchy. The gender body readed as the actor in the role. The role is performed in accordance with the manuscript he has received, while the manuscript itself is an analogy of social norms and constructions. The gender body becomes an actor who plays a role in accordance with the applicable gender law, in order to play a good role, it performs gender actions continuously and repeatedly, so that these actions establish and become gender identity. Meanwhile, the multi-sited ethnography method allows researchers to penetrate the potential of data not only on direct observation, but through other areas virtually from online sites, such as social media and Youtube sites. The data obtained successfully traced the interweaving of KSN and sinden interactions, as well as narrating the performanceivity of Apri- Mimin and Elisha built through language games. A reading of Judith Butler’s theory of gender performanceivity suggests that sinden’s performance power with the role of “male sinden duo” and “Sulawesi sinden” was built through the stereotypical imagination of gender ethnicity represented in the form of language games. On the other hand, sinden’s performanceivity is easily commodified by the puppeteer as the leader of the puppet show to gain popularity and economic benefits.AbstrakTulisan ini membahas peran dan posisi sinden dalam pertunjukan wayang kulit di era kekinian, dengan studi kasus sinden pada pertunjukan Ki Seno Nugroho. Teori performativitas gender Butler digunakan untuk melihat daya performance sinden-sinden Ki Seno Nugroho (Apri-Mimin “duo sinden banci”dan Elisha“sinden Sulawesi”). Butler dalam teorinya menyatakan bahwa performativitas gender digagas untuk membongkar persoalan hierarki konstruksi gender. Tubuh gender dibaca sebagaimana aktor yang sedang berperan. Peran tersebut dilakukan sesuai dengan naskah yang telah ia terima, sedangkan naskah sendiri adalah analogi dari norma dan konstruksi sosial. Tubuh gender menjadi aktor yang berperan sesuai dengan hukum gender yang telah berlaku, utuk dapat berperan dengan baik, ia melakukan tindakan gender secara terus menerus dan berulang, sehingga tindakan-tindakan itu menubuh dan menjadi identitas gender. Sementara itu, metode multi-sited ethnography memungkinkan peneliti merambah potensi data tidak saja pada pengamatan langsung, melainkan melalui wilayah yang lain secara virtual dari situs online, seperti media sosial dan situs Youtube. Data yang diperoleh berhasil merunut jalinan interaksi KSN dan para sinden, serta menarasikan performativitas Apri-Mimin dan Elisha yang dibangun melalui permainan bahasa. Pembacaan atas teori performativitas gender Judith Butler mengemukakan bahwa daya performativitas sinden dengan peran sebagai “duo sinden pria” dan “sinden Sulawesi” dibangun melalui imajinasi stereotipe etnisitas gender yang direpresentasikan dalam bentuk permainan bahasa. Di sisi lain, performativitas sinden dengan mudah dikomodifikasi oleh dalang sebagai pemimpin pertunjukan wayang untuk mendulang popularitas dan keuntungan ekonomi.